Bi-SO3H Functionalized Ionic Liquid Based on DABCO: New and Efficient Catalyst for Facile Synthesis of Dihydropyrimidinones - Firouzeh Nemati; Sara G. Alizadeh (Journal of Chemistry)
A simple and efficient method for the one-pot Biginelli condensation reaction of aldehydes, β-dicarbonyl compounds, and urea or thiourea employing [DABCO](SO3H)2Cl2 as a novel ionic liquid catalyst is described.